THE IMPACT OF UNEQUAL DISTRIBUTION OF TEACHERS ON THE QUALITY OF EDUCATION IN INDONESIA - Nur Innayatun; Ari Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The uneven distribution of teachers in Indonesia is a very important problem that affects the quality of education. This study aims to find out the factors that cause uneven distribution as well as what the impact is and how solutions must be done. The research method used in this study is the library research method, which is by collecting data sources in the form of journal articles, books, and documents related to the subject matter of this study. After the research data is collected, the next step is to analyze the data by reading and taking notes, then drawing conclusions. The results of this study show that the factors that cause the uneven distribution of teachers are the absence of regulations on the placement and distribution of teachers in the form of a strong legal umbrella, the weak education information data system, weak supervision and law enforcement, and the strength of the local political elite game. Meanwhile, the impact of uneven distribution of teachers is an impact on the uneven quality of education, low graduation rates, social and economic inequality, as well as a decrease in learning motivation and academic achievement of students. Thus, this research provides a solution for the government to provide better policies for teachers in remote areas, and utilize information technology for education. That way, it is hoped that the uneven distribution of teachers can be overcome so that the quality of education in Indonesia can increase evenly.